Social Networks and the Management of Water Resources for Agriculture in Rio Caia Catchment (Portugal) - Luís Rodrigues; Carlos Russo Machado; Nelson Lourenço (Italian Journal of Agronomy)
The involvement of local people in the management of scarce resources, such as water available for agriculture, is a desirable approach to address some of the difficulties in the decision-making processes. This paper reports the experience of a research team of sociologists and geographers involved in the MULINO project (Multi-sectoral, Integrated and Operational decision support system for sustainable use of water resources at the catchment scale). In the framework of this international and interdisciplinary project, a social network analysis was developed in a catchment of south Portugal. This analysis was structured in five fundamental steps: Stakeholder Identification; Data Collection; Data Treatment; Network Visualisation; and Local Network Analysis. The information was gathered mainly through a questionnaire, bibliographic references, statistical inputs and field observations. In order to obtain a typology of stakeholders and their interactions, a factorial analysis of multiple correspondences and a cluster analysis were applied. The social network analysis, which is the measuring and visualisation of relationships and flows between people, groups, organisations or other information/knowledge processing entities, supported the description of two types of patterns that link different sets of actors: social groups (sets of actors closely linked together) and social positions (sets of actors who are linked into the overall social system in similar ways). The analysis of the Caia Catchment network shows that this type of analysis is important not only as a means to characterising certain parameters about the network’s characteristics, but also as a significant tool to help improve the communication within the social network.